The diagnostic accuracy of temporal artery ultrasound and temporal artery biopsy in giant cell arteritis: A single center Australian experience over 10 years. (22nd January 2022) - He, Jianna; Williamson, Luke; Ng, Beverly; Wang, Jeremy; Manolios, Nicholas; Angelides, Socrates; Farlow, David; Wong, Peter K. K.
Abstract: Aim: To assess the diagnostic accuracy of temporal artery ultrasound compared with temporal artery biopsy and clinical diagnosis in patients with suspected giant cell arteritis (GCA) over 10 years in an Australian center. Method: Patients presenting to Westmead Hospital with possible GCA from March 2011 to December 2020 were retrospectively identified. The following parameters were obtained from the medical record: clinical presentation, inflammatory markers, temporal artery ultrasound findings, and temporal artery biopsy report. Data were assembled in a 2 × 2 table; sensitivity and specificity of temporal artery ultrasound compared with temporal artery biopsy and clinical diagnosis were calculated. Results: Over the 10‐year study period, 65 temporal artery ultrasounds were performed in 63 patients (n = 65; 61.9% female) with a mean ± standard deviation age of 69.6 ± 12.3 years. Thirteen out of 65 (20%) temporal artery ultrasounds had findings suggestive of GCA. Twenty patients (31.7%) had a clinical diagnosis of GCA irrespective of sonographic or biopsy findings. Compared with temporal artery biopsy, temporal artery ultrasound had a sensitivity of 71.4% and specificity of 93.3%. Compared with clinical diagnosis made by the treating rheumatologist, temporal artery ultrasound had a sensitivity of 55% and specificity of 95.3%. Conclusion: Temporal artery ultrasound is a useful non‐invasive investigation in the assessment of suspected GCA. If positive in the setting of a suggestive clinical presentation, a temporal artery ultrasound probably avoids the need for a temporal artery biopsy. Temporal artery ultrasound could be more widely used in the clinical management of GCA.